EFFECT OF COOPERATIVE LEARNING MODEL TYPE THINK PAIR AND SHARE (TPS) ON STUDENT COOPERATION (Quasi Experiments on Social Studies Learning Class VII in 1 Cikajang Junior High School) - Qurtubhi, Wildan Muhammad (International Journal Pedagogy of Social Studies, 2017)
Abstract-This study aims to test how much influence the model of cooperative learning type think pair and share (tps) on student cooperation (quasi experiment on social studies learning class VII in Cikajang Junior High School). The design used in this research is non-equevalent controlgroup with "before" and "after" pattern and treatment done on class VII-A as experiment class group. While VII-B as a control class group that made a comparison. Sampling used is purposive sample technique. Student cooperation data collection using closed questionnaire. After data collection, quantitative analysis is done through hypothesis or T-test. The results of differences between "before" and "after" in the experimental class given treatment showed significant improvement. In control classes between "before" and "after" that are not given treatment there is also a difference, but not an improvement but rather a decrease. So it can be concluded that there is influence of model cooperative learning type think pair and share (tps) to student's cooperation in social studies learning.Keywords: Student Cooperation, Cooperative Learning Type Think Pair and Share (TPS),Social Studies Learning